Quantification of hepatic FOXP3+ T-lymphocytes in HIV/hepatitis C coinfection - Williams, S; Donaldson, E; Van Der Kleij, T; Dixon, L; Fisher, M; Tibble, J; Gilleece, Y; Klenerman, P; Banham, A; Howard, M; Webster, D (Blackwell Publishing Ltd, 2014)
Coinfection with HIV adversely impacts every stage of hepatitis C (HCV) infection. Liver damage in HCV infection results from host antiviral responses rather than direct viral pathogenesis. Despite depressed cellular immunity, coinfected patients show accelerated hepatic fibrosis compared with HCV monoinfected patients. This paradox is poorly understood. T-regulatory (Treg) cells (CD4+ and FOXP3+) are hypothesized to limit hepatic damage in HCV. Our hypothesis was that reduced frequency of hepatic Treg in HIV/HCV coinfection compared with HCV monoinfection may explain poorer outcomes. We quantified FOXP3+, CD4+, CD8+ and CD20+ cells in liver biopsies of 35 male subjects matched by age and ISHAK fibrosis score, 12 HIV monoinfected, 11 HCV monoinfected and 12 HIV/HCV coinfected. Cell counts were performed using indirect immunohistochemical staining and light microscopy. HIV/HCV coinfected subjects had fewer hepatic FOXP3+ (P = 0.031) and CD4+ cells (P = 0.001) than HCV monoinfected subjects. Coinfected subjects had more hepatic CD8+ cells compared with HCV monoinfected (P = 0.023), and a lower ratio of FOXP3+ to CD8+ cells (0.08 vs 0.27, P < 0.001). Multivariate analysis showed number of CD4+ cells controlled for differences in number of FOXP3+ cells. Fewer hepatic FOXP3+ and CD4+ cells in HIV/HCV coinfection compared with HCV monoinfection suggests lower Treg activity, driven by an overall loss of CD4+ cells. Higher number of CD8+ cells in HIV/HCV coinfection suggests higher cytotoxic activity. This may explain poorer outcomes in HIV/HCV coinfected patients and suggests a potential mechanism by which highly active antiretroviral therapy may benefit these patients. © 2013 John Wiley and Sons Ltd.